Multiobjective Optimization Methodology : A Jumping Gene Approach - K.S. Tang ... [et al.]. (Boca Raton : CRC Press, 2012)
Discovered by Nobel Laureate, Barbara McClintock in her work on the corn plants in the nineteen fifties, the phenomenon of Jumping Genes has been traditionally applied in the bio-science and bio-medical fields. Being the first of its kind to introduce the topic of jumping genes outside bio-science/medical areas, this book stands firmly on evolutionary computational ground. Requiring substantial engineering insight and endeavor so that the essence of jumping genes algorithm can be brought out convincingly as well as in scientific style, it has to show its robustness to withstand the unavoidable comparison amongst all the existing algorithms in various theories, practices, and applications. As a new born algorithm, it should undoubtedly carry extra advantages for its uses, where other algorithms could fail or have low capacity--
1. Introduction -- 2. Overview of multiobjective optimization -- 3. Jumping gene computational approach -- 4. Theoretical analysis of jumping gene operations -- 5. Performance measures on jumping gene -- 6. Radio-to-fiber repeater placement in wireless local-loop systems -- 7. Resource management in WCDMA -- 8. Base station placement in WLANs -- 9. Conclusions.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Multiple criteria decision making; Mathematical optimization; Genetic algorithms; Biotechnology -- Mathematical models; Electronic books